PENGARUH AROMATERAPI LAVENDER TERHADAP INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF - Abnurama, Lu'lu Nabila; Putri, Ratna Dewi; Yantina, Yuli; Amirus, Khoidar (Universitas Malahayati Bandar Lampung, 2021)
Introduction : Labor pain is inherent physiology and is felt by every mother in labor. Pain management in labor with non-pharmacological methods is Aromatherapy, the aroma of essential lavender can provide comfort and relaxation to the body and mind of the mother, can stimulate the release of endorphin hormones so as to relieve labor pain. This study aims to determine the effect of lavender aromatherapy on the intensity of labor in the first phase of active labor in PMB. Mardiana, S.ST, Kec.Menggala, Kab. Tulang Bawang 2019.Research methods : This type of research is quantitative, with a research design Quasi Experiment Design using the design of Two Group Pre-Post Test Design. The sampling technique used is Non Probability Sampling with Accidental Sampling techniques. This study uses a minimum sample of experimental research that is as many as 15 respondents per group (15 experimental groups and 15 control groups) to mothers in the first phase of active phase, where data collection uses observation sheets and SOP. Analysis of the data used is the Independent Sample T Test.Results and Conclusions : From the results of research conducted by the author, it is known that the average value of labor pain intensity in the experimental group (Lavender Aromatherapy) was 5.27 (moderate pain), while in the control group results the average pain intensity was 7.53 (pain severe / severe) and a significance value of 0.000, P value α α (0.05) means that there is an influence of Lavender Aromatherapy on the intensity of labor pain during the active phase. The use of essential oils by inhalation is a fast, simple, and effective way to get the benefits of treatment. This non-pharmacological therapy provides many advantages and does not cause side effects or interference with the mother and fetus so lavender can be used as an alternative for the management of labor pain by midwives to improve service quality. Keywords : Labor pain, Lavender Aromatherapy.